Microclimate evaluation of a new design of insect-proof screens in a Mediterranean greenhouse - Lopez-Martinez, Alejandro; Valera Martínez, Diego L.; Molina-Aiz, Francisco; Peña-Fernandez, Araceli; Marín-Membrive, Patricia (Spanish Journal of Agricultural Research, 2014)
This work studies natural ventilation in a Mediterranean greenhouse, comparing a new experimental screen of 13×30 threads cm-2 (porosity 39.0%) with a commercial control screen of 10×20 threads cm-2 (porosity 33.5%). In addition, both screens were tested in a wind tunnel to determine the discharge coefficients Cd of the greenhouse side and roof vents, which proved to be 0.16 for the commercial control screen and 0.18 for the experimental screen at both vents. These values represent a theoretical increase of 11% (Cd,φ-10×20 /Cd,φ-13×30 = 0.89) in the natural ventilation capacity of the greenhouse when the experimental screen is used. The greenhouse was divided into two separate sections allowing us to analyze natural ventilation in both sectors simultaneously. Air velocity was measured in the lateral and roof vents with two 3D and six 2D sonic anemometers. Using the commercial control screen there was an average reduction of 16% in ventilation rate, and an average increase of 0.5ºC in the average indoor air temperature, compared to the experimental screen. In addition, the ventilation efficiency ηT was higher with the experimental screen (mean value of 0.9) than with the control (mean value 0.6). We have designed an experimental insect-proof screen (13×30 threads cm-2) with smaller thread diameter, higher thread density, smaller pore size and higher porosity than are used in most commercial meshes. All of these factors promote natural ventilation and improve the greenhouse microclimate.